Electrical Component Measurement, Mechanics and Optics in Fundamental Physics - Laboratory Manual Volume-II - Walelgn, Anteneh Yesigat (Electrical Component Measurement, Mechanics and Optics in Fundamental Physics - Laboratory Manual Volume-II, 2024)
This fundamental laboratory manual from Volume II is provided on the experimental theory for the higher educational level that is especially triggered by the electromagnetic characteristics and nature of their components, such as capacitors, resistors, oscilloscopes, magnetism, and AC-circuits, into an experimental approach to be performed in the pre-college and higher levels. This manual gives the necessary details to perform the experiments. The experiments included are meant to offer a basic understanding of electronics and the magnetic concept of physics. Most of the experiments are designed to go hand in hand with the theoretical courses in physics being taught during the whole curriculum of the semesters. For some additional experiments away from the theoretical background of the experiment, the laboratory procedure and data sheet are arranged for each experiment session and are contained both in the previous Volume I and this Volume II books. Some additional experiments away from the theory courses are being raised to enhance the scope of learning beyond the interdisciplinary physics courses that will integrate science with technology. The necessary theory for this type of experiment is described in the manual in a self-explanatory manner. However, all efforts are made to clarify any doubts by the teachers in these laboratory classes.